Diabetes Epidemic’ in Germany? A Critical Look at Health Insurance Data Sources - Hoffmann, F.; Icks, A. (Experimental and Clinical Endocrinology & Diabetes, 2012)
The German diabetes prevalence is considered to be one of the highest in Europe. It is often estimated based on claims data of a regional health insurance (Allgemeine Ortskrankenkasse; AOK). We studied the prevalence of diabetes within AOK members compared to other types of funds.We pooled data of the German National Telephone Health Interview Surveys 2003 and 2004 comprising a nationally representative sample of 15 354 adults aged 18 years and older. We first estimated the crude prevalence of diabetes stratified by funds. To analyze the association between diabetes prevalence and membership in different health insurance funds, we fitted logistic regression models and stepwise adjusted for age, sex, region, comorbidities, anthropometric measures, and lifestyle variables.The overall prevalence of diabetes was 6.5%. Compared to all other statutory health insurance funds, the prevalence of diabetes was nearly twice as high within the AOK (10.1% vs. 5.4%; Odds Ratio [OR]: 1.96; 95% confidence interval [CI]: 1.67–2.31). Although continuously decreasing, significant differences remained after controlling for demographic variables (OR: 1.62; 95% CI: 1.38–1.90) and in the fully adjusted model (OR: 1.36; 95% CI: 1.14–1.62). Persons privately insured had a prevalence of 4.8%, which was not significantly different than for members of statutory health insurance funds other than the AOK.The prevalence of diabetes was roughly twice as high in the AOK compared to all other statutory health insurance funds. The estimated German prevalence of diabetes is likely to be too high when it is based on these data.
Keywords: diabetes mellitus; prevalence; international comparison; health insurance claims data